Sistem Pengawasan PLBN Motain Terhadap Aktivitas Masyarakat Dalam Mencegah Terjadinya TPPO - Alexander Reynaldi Koli; Florensiana Resi Ngepi; Yohanes Arman (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Borders are often defined as the boundaries of political territory and residential space. In some cases, borders have a broader meaning for geographical political and economic conditions with certain cases of dividing power over bordering areas suggesting that border areas are always described as lagging areas. The research method that the author uses is normative juridical research method this study uses the approach of the problem of legislation approach related to what is to be examined by the researcher. The data and information of this research are primary and secondary data which are data that have been available through legislation, journals, books, and other factual supporting sources. Sex workers and sex exploitation, domestic workers (PRT), migrant workers, and brides-to-be are the most common types of work targeted by human trafficking. This happens through border areas . A policy is needed to address this problem, not the small, unplanned steps that have been taken so far. Bilateral or multilateral cooperation is needed to address different approaches to the management and interests of human trafficking.To solve the problems and efforts to maintain the defense and security of the country, of course, must begin with the affirmation of the land border by both countries. The potential for the emergence of transnational organized crime in the border region is relatively high so that the cooperation and active role of all stakeholders is needed.The construction of integrated cross-border posts, the deployment of TNI border security maintenance task forces on the border and outer islands, as well as coordinated patrols with neighboring countries.